Computerized cognitive rehabilitation in patients with multiple sclerosis (MS): A systematic review and meta-analysis - Abdorreza Naser Moghadasi; Omid Mirmosayyeb; Sara Bagherieh; Mohammad ali Sahraian; Mahsa Ghajarzadeh (Caspian Journal of Internal Medicine)
Background: Cognitive impairment (CI) is one of the main features of multiple sclerosis (MS). Cognitive rehabilitation (CR) programs are crucial for improving cognition and computer-assisted cognitive rehabilitation is considered as an effective method for cognition rehabilitation. To assess the effects of computer-based cognitive rehabilitation program on cognition in patients with multiple sclerosis (MS). Methods: We performed a comprehensive search in PubMed, Scopus, Web of Science, EMBASE, and Google Scholar databases along with gray literature up to September 2021. Randomized clinical trials, articles had been published in the English language. We evaluated the risk of potential bias via the Cochrane Collaboration's tool for assessing the risk of bias. Standardized mean difference (SMD) was calculated. Results: The preliminary search retrieved 2302 articles by literature search, after deleting duplicates 2248 remained.  Eight articles remained for meta-analysis. Totally, 235 patients in intervention group and 192 in control group were evaluated. Mean age ranged from 43.5-52 years. The SMD of PASAT (Paced Auditory Serial Addition Test) (Case-control) test was 0.35 (95%CI:0.1-0.66) (I2:24.4%, P=0.2). The SMD of SDMT (Case-control) test was 0.07 (95%CI:-0.18-0.33). The SMD of PASAT before and after intervention in case group was 0.68 (95%CI:0.45-0.91) (I2:40%, P=0.15). The SMD of SDMT before and after intervention in case group was 0.44 (95%CI:0.21-0.66) (I2:40%, P=0.15). Conclusions: The results of this systematic and meta-analysis showed that computerized cognitive rehabilitation program is effective in improving PASAT score.